P3DM: Mapping out the future of Indigenous Peoples in 3D - Bersalona, Rino B. (Technical Centre for Agricultural and Rural Cooperation, 2004)
Rino B. Bersalona and Kail M. Zingapan explain how indigenous communities in the Philippines are using GPS and relief models to reclaim their ancestral territories. Through an innovative process known as participatory 3D modelling (P3DM), they have mapped